2022
DOI: 10.3846/jeelm.2022.16333
|View full text |Cite
|
Sign up to set email alerts
|

Public Values Regarding an Urban Mangrove Wetland in the United Arab Emirates

Abstract: Mangrove wetlands are facing an existential threat from rapid socio-economic development. In this study, public environmental values regarding mangrove wetlands in the Ras Al Khaimah (RAK) city in the United Arab Emirates were assessed, considering gender, age, education, income, length of residency in RAK, knowledge of RAK mangrove and awareness of sustainability. A population sample of 427 respondents were face-to-face interviewed. Results suggest that mangrove value orientations are highly associated with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…In the UAE it has been determined that the most vulnerable ecosystems to climate change are water, coastal, marine, and dryland ecosystems, in addition to sectors such as building and infrastructure; agriculture and food security, and public health [85]. It is also suggested that the mangroves in the Arabian Gulf will be threatened by changes such as the decrease in rainfall due to climate change [86]. There is still limited data supporting the potential consequences of climate change on the UAE's wetlands, making this study an important baseline for future studies.…”
Section: Management Of the Reservementioning
confidence: 99%
“…In the UAE it has been determined that the most vulnerable ecosystems to climate change are water, coastal, marine, and dryland ecosystems, in addition to sectors such as building and infrastructure; agriculture and food security, and public health [85]. It is also suggested that the mangroves in the Arabian Gulf will be threatened by changes such as the decrease in rainfall due to climate change [86]. There is still limited data supporting the potential consequences of climate change on the UAE's wetlands, making this study an important baseline for future studies.…”
Section: Management Of the Reservementioning
confidence: 99%